An Examination of Factors Influencing Turnover Intentions Among Generation Z Employees - Daniel, Daniel; Sanjaya, Regi (STIE Ekuitas, 2024)
Introduction/Main Objectives: Gen-Z has started to take over the workforce both worldwide and in Indonesia. In particular, West Java and the city of Bandung have the highest numbers of Gen-Z workers and residents. Background Problems: However, challenges arise when Gen-Z workers frequently change jobs and move on from their positions. Novelty: This paper represents the first qualitative study investigating the factors that influence turnover intentions among Gen-Z employees in Bandung city. Research Methods: This research employs a qualitative and descriptive approach to provide a clear understanding of the causes or factors behind turnover intention, using interviews and observations. A total of 12 individuals from various industries in Bandung served as informants for this study. Finding/Results: 9 out of the 12 respondents interviewed reported experiencing more than one factor influencing their turnover intentions. These factors are interconnected, forming primary and secondary influences. The most common reasons driving Gen-Z employees’ desire to leave their jobs include heavy workloads linked to multiple job responsibilities, dissatisfaction with compensation, high work intensity, toxic work culture and leadership, and a lack of supportive work environment. Conclusion: This research aims to encourage companies to implement effective and suitable staffing practices. By analyzing job positions and creating clear job descriptions, companies can avoid overlapping responsibilities. Additionally, placing competent leaders can help prevent toxic work cultures and foster a supportive environment for Gen-Z employees, ultimately reducing their intention to leave the company.